El Tahuantinsuyo: expansin, organizacin administrativa e importancia - Lopez Hilario, Griced Lisbeth (2019)
The Tahuantinsuyo as part of the process of the History of Peru, was one of the main empires of America in the same degree of priority as the Central American cultures. It was developed in the fifteenth century, prioritizing its expansion from the Ancasmayo river in Colombia to the north and the Maule river in Chile to the south; This expansion was due to the correct administrative organization that they carried out for the function of each of its members. As was the creation of the road network of roads to keep the main city CUSCO connected with the rest of the conquered towns, the creation of a system of administrators such as the members of the conquering army, the tucricuq, quipucamayoc, collcas, etc. That they exercised the function of providing the Inca state and ensuring the order and fulfillment of the orders of the Incas. We must also prioritize that domain and control by the Incas who achieved this expansion process, which were Pachacutec, Tpac Inca Yupanqui and Huayna Cpac; Main Incas of the expansion process in Tahuantinsuyo. This session reflects the important moments of the learning process about one of the most important empires in the history of Peru, within the process of expansion.